2015
DOI: 10.5755/j01.ee.26.2.3863
|View full text |Cite
|
Sign up to set email alerts
|

Research of Experience of Emigration for Employment and Education Purposes of Students

Abstract: The scale of emigration of the Lithuanian population is among the highest in the EU, the number of residents in the country, including children and youth under 15 years of age departing with adults, shows a decreasing trend, but the emigration of students of higher education institutions is especially alarming. The growing emigration flows to the countries with developed economies are associated with the disbalance of labour force between the supply and demand of labour in the countries of different economic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Growing importance of the mobility factors in contemporary economies is unquestionable (Kumpikaite & Zickute, 2012;Janotka et al, 2013, Berzinskiene et al, 2014Kvedaraite et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Growing importance of the mobility factors in contemporary economies is unquestionable (Kumpikaite & Zickute, 2012;Janotka et al, 2013, Berzinskiene et al, 2014Kvedaraite et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of economic determinants on migration is widely addressed in the literature (Lucas, 1990;Lundborg, 1991;Arnold, 1992;Teitelbaum & Russell, 1992;Faini and Venturini, 1993;Schiff, 1994;Martin & Taylor 1996;Durand et al, 1996;Kim & Cohen, 2010;Kumpikaite & Zickute, 2012;Janotka et al, 2013, Berzinskiene et al, 2014Kvedaraite et al, 2015). The vast majority of papers, however, provide evidence explaining only one-directional type of relationships that exist between different variables under consideration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is what determines the migration destination. For Kvedaraite et al (2015); Mihi-Ramireza and Kumpikaite (2014) and Janotka et al (2013), economic factor has been identified as the major reason students' migration decision. Students considered also the world ranking of universities in their choice of destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The highly-skilled migration is an important, international and growing issue of the last decades (Kazlauskiene & Rinkevicius, 2006;Arslan et al, 2014;Kvedaraite et al, 2015).…”
Section: Introductionmentioning
confidence: 99%